Implementation of “Si Pemenang” (Sistem Pembelajaran Renang) Application to Improve Chest Style Swimming Learning Outcomes (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2025)
This research aims to address the challenge of comprehending swimming material, which students at SMP Negeri 7 Pati find to be difficult. This difficulty arises from the complexity of the process. The process cannot be understood solely through books or worksheets. Additionally, there is a lack of optimized learning strategies and in-depth material on the techniques. The study utilized a quantitative approach with a quasi-experimental design involving 34 students from class VIII H, divided into two groups for pretest-posttest control. The research instrument contained evaluations on affective, cognitive, and psychomotor aspects of breaststroke swimming. Data analysis was conducted using the paired sample T test. The research results, analyzed with IBM SPSS 23, indicated that the experimental group had a statistically significant difference. (2-tailed) = 0.000, indicating p < 0.05, showing a significant 47% increase in learning outcomes in breaststroke swimming material. As a result, Ho1 is rejected and Ha1 is accepted. The control group exhibited a significant level in comparison. (2-tailed) = 0.789, with p > 0.05, indicating a lack of significant increase in learning outcomes. Thus, Ho1 is accepted and Ha1 is rejected. In conclusion, the Si Juara application has positively impacted breaststroke swimming learning outcomes at SMP N 7 Pati, resulting in a notable improvement. Future researchers should focus on enhancing learning models to optimize learning results